(untitled) (Journal of Geography and Environmental Management, 2019)
Determining the parameters of maximum runoff is an important water management task. Characteristics of the maximum runoff of a spring flooding are widely used in the design and operation of hydraulic engineering constructions. Characteristics of the maximum runoff of the rivers of the basin of the Elek River require specification taking into account data of the last 30-40 years. Data on an annual water runoff, a layer and the maximum runoff of a spring flooding on the rivers to the basin of the Elek River are collected. The settlement period for series of observations (1940-2015) is chosen, series of observations on 13 gauging station with use of the regression analysis are restored, the natural water runoff of the Elek and Kargala Rivers taking into account the regulating influences of reservoirs is restored, tables of the restored series with the regression equations are made; graph of dependence of the maximum water discharge on a runoff layer are received, it is made calculation accuracy assessment of key parameters of a runoff taking into account information volume equivalent to data monitoring, the table of statistical parameters of the maximal runoff is made and comparison of parameters of a curve of distribution of the maximum runoff of a spring flooding of the rivers of the basin of Elek of two periods of 1940-1974 and 1975-2015 are made.